Resolusi Konflik Islam Arus Utama Dan Ahmadiyah Di Kudus - Putri, Stephany Novalia Amanda; Nuruddin, Muhammad Subhan; Pertiwi, Indah Setyowati; Sari, Naning Intan; Noor, Aditia Muhammad (At-Tuhfah : Jurnal Studi Keislaman, 2025)
In several countries where most of the population is Muslim, there has been heated discussion about the conflict between Mainstream Islam and the Ahmadiyah group. Many conflicts between the two occur as a result of different opinions and views regarding Islamic teachings. The Ahmadiyah group is often considered a deviant Islamic group. This conflict has been discussed by Gionopulos & Mitchel/Axel Honeth. The discussion contained conflict resolution between Mainstream Islam and the Ahmadiyah group. The difference of opinion between the Mainstream Islamic group and the Ahmadiyah group began with the difference in the views of the Ahmadiyah group who considered that the Prophet Muhammad was not the last prophet. As a result of this opinion, the Ahmadiyah group has received a lot of discrimination and persecution in various countries, for example Pakistan, Indonesia, and Bangladesh. Even so, the number of followers of the Ahmadiyah group is very large because Ahmadiyah has succeeded in building a positive image in society. Apart from that, Ahmadiyah also has strong beliefs about peace, love, and tolerance. The movement of the Ahmadiyah group spreads Islam peacefully, but they have the belief that there is a prophet after the Prophet Muhammad, named Ahmad. There have been many restrictions on Ahmadiyah activities in Indonesia. Ahmadiyah itself arrived in Indonesia in 1923. This article focuses on the Ahmadiyah group in Kudus because in this area Ahmadiyah received a positive response from the community. Currently the government of Kudus City is monitoring the Ahmadiyah group in the area. Ahmadiyah in Kudus has a conflict resolution strategy by providing an understanding that their group is not heretical.